Silly idol (2016)
Living in a context where the image defines much about the personality and identity of things, appearance defines how the people understand an idea at first sight. This appearance is followed by various attitudes which reinforce de idea of identity, creating by these means a personalized description of individuals and things. In this way, we as individuals take certain personalities in different moments of our lives which define our behaviour in society, which are in general mediated by our interests and personal preferences. Inverting this process, we can act in certain ways thus creating a given appearance with a finality in mind: the people that interact with this individual create a personal idea of him by what he can appreciate from his social and common performance which happens in a daily basis.